On the possibility of controlling the morphology of carbon-containing titanium dioxide-based nanocomposites during pulsed plasma chemical synthesis; Fullerenes, Nanotubes and Carbon Nanostructures; Vol. 27, iss. 9 - Sazonov R. V. Roman Vladimirovich; Kholodnaya G. E. Galina Evgenievna; Ponomarev D. V. Denis Vladimirovich; Konusov F. V. Fedor Valerievich; Gadirov R. M. Ruslan Mukhamedzhanovich; Zhirkov I. S. Igor Sergeevich (2019, 2019)
Title screen